Full-duplex user-centric communication using non-orthogonal multiple access - Sock Theng Ooi; Razali Ngah; Marwan Hadri Azmi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper proposes an improved user-centric Non-Orthogonal Multiple Access (NOMA) communication in two-base station networks with in-band full duplex (IBFD) user. We derive the achievable rates of the proposed user-centric NOMA systems. For benchmarking purposes, we also derive the achievable rate for the user-centric system deploying conventional NOMA schemes, Orthogonal Multiple Access (OMA) schemes and point-point communication systems. We then analyze and simulate the performance of the proposed and all the benchmarked systems. We found that our proposed user-centric NOMA approach has a 64% improvement in the total achievable rate when compared to the benchmarked approach under similar power constraint.